Electric power systems state estimation using SCADA and PMU measurements - Alcaide Moreno, Boris Adrián (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
This thesis proposes an approach to incorporate the mathematical models of wind turbine generators, automatic load frequency controls as well as voltage magnitude and frequency dependent loads into a weighted least squares-based state estimation algorithm suitable for the analysis of flexible AC transmission systems. As opposed to conventional static state estimators, where the inclusion of these electric components has been neglected so far, the proposed approach permits the determination of the steady state operation of a power system in the event of a supply-demand unbalance by estimating the magnitude of the frequency deviation from its nominal value. The state estimation is based on measurements related to those that should be obtained by a Supervisory Control and Data Acquisition (SCADA) system and Phasor Measurement Units (PMU). For purpose of this thesis, the set of values associated with SCADA measurements and PMU measurements are generated from a power flow analysis of the network under study. The computational burden of processing a large set of measurements collected from large-scale power systems is reduced by performing a multi-area state estimation based on measurements provided by a SCADA system and phasor measurement units. This thesis also proposes a novel tracking state estimator which simultaneously processes SCADA measurements as and when they arrive to the control center along with a limited number of synchrophasor measurements. The time skew effects are reduced by only processing the SCADA measurements received since the last execution of the estimator. In order to assure observability, after each execution all SCADA measurements are forecasted and used as pseudo-measurements in the next estimation.

En esta tesis se propone un método para incorporar los modelos matemáticos de generadores eólicos, controles de frecuencia, así como también cargas dependientes de voltaje y frecuencia en un algoritmo de mínimos cuadrados ponderados desarrollado para el análisis de los sistemas de transmisión flexible de corriente alterna. A diferencia de los estimadores de estado estático convencionales, donde la inclusión de estos componentes eléctricos no había sido considerado hasta ahora, la investigación propuesta permite la determinación de la operación en estado estacionario de un sistema de potencia en el caso de un desequilibrio de oferta y demanda mediante la estimación de la magnitud de la desviación de frecuencia a partir de su valor nominal. Los estimadores de estado utilizan mediciones obtenidas mediante un sistema de control supervisorio y adquisición de datos (SCADA) y unidades de medición de fasores (PMU), sin embargo, para propósito de esta tesis, el conjunto de valores asociados con las mediciones SCADA y las mediciones de PMUs se generan a partir de un análisis de flujo de potencia de la red bajo estudio. La carga computacional de procesar un amplio conjunto de mediciones se reduce mediante la implementación de una estimación de estado multi-área. Se propone además, un nuevo estimador de estado de seguimiento que procesa simultáneamente mediciones SCADA cuando estas llegan al centro de control, junto con un número limitado de mediciones de sincrofasores. Solamente se procesan las mediciones SCADA recibidas desde la última ejecución del estimador con el objetivo de evitar procesar información recolectada mucho tiempo atrás, y esto degrade el desempeño del estimador de estado.
Facultad de Ingeniería Eléctrica. Doctorado en Ciencias en Ingeniería Eléctrica
Keywords: info:eu-repo/classification/cti/7; FIE-D-2016-0330; Estimación de estado; SCADA; PMU; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3361